DIGITAL NEURO-FUZZY CONTROL OF LINEAR HIGH-CURRENT ELECTRON ACCELERATOR UNITS - Udovenko, S. G.; Shamraev А. А.; Dibe, G. (Radio Electronics, Computer Science, Control, 2024)
In the work the control structure is offered and the digital control methods for the linear accelerator blocks with use of fuzzy and artificial neural networks models are developed. The simulation data is confirmative efficiency of the considered methods.